Hearing impairment, cochlear morphology, and peroxynitrite (ONOO−) formation in adult and aging NOS II knockout mice. (2nd October 2016) - Labbé, Daniel; Bloch, Wilhelm; Schick, Bernhard; Michel, Olaf
Abstract: Conclusion: Nitric oxide synthase (NOS) II induction is a protective mechanism against age-related degeneration of the cochlea. Objectives: An induction of NOS II has been described in different inner ear pathologies. The objective was to examine the role of NOS II in age-related degeneration of the cochlea. Methods: The hearing ability in adult and aging NOS II knockout mice (KO) and their wildtype (WT) littermates was explored via auditory brainstem response (ABR) measurements. Inner ear morphological differences were studied with scanning electron microscopy (SEM). Immunohistochemistry was used to examine the induction of NOS II in the inner ear of aging WT mice. Expression of nitrotyrosin, a marker protein for the reactive oxygen species peroxynitrite, was compared between KO and WT mice using immunohistochemistry. Results: Adult KO mice exhibited a mild hearing impairment. WT mice showed an induction of NOS II after 6 months of age. Age-related hearing deterioration was accelerated in KO mice, which was accompanied by increased nitrotyrosin formation and outer hair cell loss.